Measurement and evaluation in the secondary schools : a handbook. (Makati City, Philippines : Department of Education, Culture and Sports, 1990)
This handbook is for the secondary school administrators and teachers who have expressed their need for a practical guide in the evaluation and measurement on instruction in the high school. It is intended specifically to aid the classroom teacher who has to continuously assess student learning both for making marking purposes and for acquiring feedback that can serve as basis for the improvement of teaching and learning in the classroom.
Part I. Basic concepts -- 1. Concepts in evaluation -- 2. Approaches to evaluation -- 3. The Uses of test -- 4. Types of test -- 5. Test construction -- 6. Evaluation of affective tests skills -- 7. Evaluation techniques and instruments -- 8. Evaluation of psychomotor skills -- 9. Converting skills to grades -- Part II. Sample test items.
Includes bibliographical references.
Keywords: EDUCATION